Dampak Sistem Akuntabilitas Kinerja Instansi Pemerintah Atas Kompetensi Dan Sistem Pengendalian Intern - Abdul Aziz; Endah Susilowati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to examine the effect of the government's internal control system and human resource competence on the performance accountability system of government agencies. The independent variables in this study are the government's internal control system, human resource competence, and the dependent variable is the government agency's performance accountability system. This research was conducted on all employees of the sidoarjo regency social service. The research method used in this research is quantitative and the type of data used in this research is primary data with the data collection method in the form of a questionnaire. The population in this study were employees of the sidoarjo regency social service, and the sample selection was carried out using the saturated sampling method and obtained data from 33 employees used in this study. This study uses SEM-PLS to test several hypotheses. The results of the study show that the government's internal control system influences the performance accountability system of government agencies. Human resource competence influences the performance accountability system of government agencies. Keywords: Government's Internal Control System, Human Resource Competence, Performance Accountability System Of Government Agencies.